Ars '74. - Tampereen Taidemuseo, Tampere; Ars 74 (Helsinki : Ateneum - The Fine Arts Academy of Finland, 1974)
Aillaud, Gilles ; Pearlstein, Philip ; Segal, George ; Katz, Alex ; Morley, Malcolm ; Billgren, Ola ; Franzen, John-e ; Friberg, Roj ; Csernus, Tibor ; Blackwell, Tom ; Clarke, John Clem ; Close, Chuck ; Cottingham, Robert ; Eddy, Don ; Estes, Richard ; Flack, Audrey ; Goings, Ralph ; Johnson, Guy ; Kacere, John ; Kanovitz, Howard ; McLean, Richard ; Ott, Jerry ; Mahaffey, Noël ; Parrish, David ; Salt, John ; etc.
Ars '74, Ateneum - The Fine Arts Academy of Finland, Helsinki, 15.2. - 31.3.1974 ; Ars '74, Tampereen Taidemuseo, Tampere, 10.4. - 12.5.1974
boek